Production and diversity of microorganisms associated with sinking particles in the subtropical North Pacific Ocean. Issue 9 (2nd July 2021) - Church, Matthew J.; Kyi, Eint; Hall, Robert O.; Karl, David M.; Lindh, Markus; Nelson, Alexa; Wear, Emma K.
Abstract: Sinking particulate organic matter controls the flux of carbon (C) from the surface ocean to the deep sea. Microorganisms actively colonize particles, but the extent to which microbial metabolism influences particle export remains uncertain. We conducted experiments to quantify rates of bacterial production (derived based on 3 H‐leucine incorporation) and dark C‐fixation (based on 14 C‐bicarbonate assimilation) associated with sinking particles collected from the base of the euphotic zone (175 m) in the subtropical North Pacific Ocean. Seawater was amended with sinking particles and rates of filter size‐fractionated (0.2, 2, and 20 μ m) bacterial production and dark C‐fixation were measured. Sequencing of 16S ribosomal RNA (rRNA) gene amplicons revealed that microorganisms in the particle‐amended treatments differed from those in the unamended seawater controls, with the particle treatments enriched in putative copiotrophic bacteria. The addition of sinking particles increased rates of bacterial production (by 6‐ to 9‐fold), and to a lesser extent dark C‐fixation (by 1.7‐ to 4.6‐fold), relative to unamended controls, with most of the production associated with filter pore sizes < 20 μ m. Normalizing production to concentrations of particulate C yielded rates that were statistically indistinguishable between particle‐amended treatments and unamended controls. We then examined possible relationships between sinking particulate C flux attenuation and its supply to the mesopelagic waters, revealing that flux attenuation was positively related to increases in particulate C supply. Together with results from our experiments, we suggest processes that contribute to sinking particle disaggregation both increase flux attenuation and favor microbial mineralization of particle‐derived organic matter.